EFFECT OF SUB LETHAL CONCENTRATION OF ZINC ON GROWTH AND SURVIVAL OF DAPHNIA - Kumar, Kanchan; Tiwari, V. K.; Dube, Kiran; Prakash, Chandra; Verma, A. K.; Rani A.M., Babitha (Journal of Indian Fisheries Association, 2014)
The effect of zinc on growth and survival of Daphnia has been studied in detail. Neonates of Daphnia were exposed to different water – borne zinc concentrations. Although zinc toxic at high concentrations, is is also an essential element required for many biological processes. Zinc it vital metal for Daphnia for normal development and reproduction. Mass culture of Daphnia was done in plastic tubs. In the present experiment, the effect of zinc on Daphnia was studied at an exposure equivalent to the 48 hr LC50. Based on the LC50, seven Zn2* levels (prepared through serial dilution from a stock solution of 5 mgL‑1) for the chronic toxicity tests were selected. These were: 0,0.05, 0.10, 0.20, 0.40, 0.80 and 1.60 mgL-1 of Zn+2. The population density of Daphnia got increased with increase of sub-lethal dosages of zinc (up to 0.4 mgL-1) and became negative form of zinc and decreased significantly at higher toxic dosages (0.8 mgL-1 onwards), indicating that zinc is required as micronutrient for stimulating reproduction and hence growth in terms of population density. Key words: Daphnia, toxicity, sub lethal effects.